Co-production of the shale gas publics in Poland and the negotiation of the state citizens relations. Issue 4 (November 2018) - Lis, Aleksandra
Highlights: The paper reflects on a socio-political reality that was co-produced by the shale gas development project in Poland. It examines co-production of publics and the issue of shale gas development. It examines political implication of scaling publics and issues to the state-citizens relations. Abstract: The paper explores the emergence of different publics for shale gas issue along the development of exploration activities in Poland. Through the concept of co-production, it is argued that publics do not pre-exist socio-technical realities but that they are organized by various actors together with these realities. The paper argues that scaling is an important aspect of the co-production of publics as it helps to navigate among them and the issues they represent and govern them according to their scalar relevance: local, regional, national or international. As political realities, publics become important terrains within which relations between state and citizens are negotiated.